Urgensi pendidikan akidah bagi generasi z dalam menyikapi krisis keimanan masa kini - Nisa', Khoirun (Maliki Interdisciplinary Journal, 2025)
Faith education plays a strategic role in shaping character and strengthening the spiritual resilience of the younger generation, particularly Generation Z, who are growing up in the digital and globalized era. This article examines the urgency of faith education in responding to contemporary challenges such as secularism, the influence of social media, religious pluralism, as well as moral degradation and modern lifestyles. Using a qualitative approach, the findings suggest that a deep understanding of Islamic creed serves as a fundamental foundation for maintaining spiritual integrity while fostering individuals who are tolerant, critical, and adaptive to the dynamics of the times. Therefore, the implementation of contextual and innovative faith education is essential to ensure that the values of belief remain deeply rooted in students, enabling them to face global challenges without losing their religious orientation.